Core-Shell Nanofibrous Scaffold Based on Polycaprolactone-Silk Fibroin Emulsion Electrospinning for Tissue Engineering Applications - Trina Roy; Priti Prasanna Maity; Arun Prabhu Rameshbabu; Bodhisatwa Das; Athira John; Abir Dutta; Sanjoy Kumar Ghorai; Santanu Chattopadhyay; Santanu Dhara (Bioengineering, 2018)
The vast domain of regenerative medicine comprises complex interactions between specific cells’ extracellular matrix (ECM) towards intracellular matrix formation, its secretion, and modulation of tissue as a whole. In this domain, engineering scaffold utilizing biomaterials along with cells towards formation of living tissues is of immense importance especially for bridging the existing gap of late; nanostructures are offering promising capability of mechano-biological response needed for tissue regeneration. Materials are selected for scaffold fabrication by considering both the mechanical integrity and bioactivity cues they offer. Herein, polycaprolactone (PCL) (biodegradable polyester) and ‘nature’s wonder’ biopolymer silk fibroin (SF) are explored in judicious combinations of emulsion electrospinning rather than conventional electrospinning of polymer blends. The water in oil (W/O) emulsions’ stability is found to be dependent upon the concentration of SF (aqueous phase) dispersed in the PCL solution (organic continuous phase). The spinnability of the emulsions is more dependent upon the viscosity of the solution, dominated by the molecular weight of PCL and its concentration than the conductivity. The nanofibers exhibited distinct core-shell structure with better cytocompatibility and cellular growth with the incorporation of the silk fibroin biopolymer.